Some Known Results and an Open Problem of Tree - Wheel Graph Ramsey Numbers - Surahmat (Pusat Publikasi Ilmiah LPPM Institut Teknologi Sepuluh Nopember, 2005)
There are many famous problems on finding a regular substructure in a sufficiently large combinatorial structure, one of them i.e. Ramsey numbers. In this paper we list some known results and an open problem on graph Ramsey numbers. In the special cases, we list to determine graph Ramsey numbers for trees versus wheels.